Trajectoires d’adaptation face au changement climatique : analyse et transformation du système de gouvernance du massif ardennais - Jon Marco Church (Revue de Géographie Alpine)
The Ardennes are a mountain forest area in the heart of Europe. It is fundamental for this mountain area to be able to anticipate climate change and its expected impacts. In this article, we are particularly interested in the Ardennes governance system. We first use transformational sustainability research methods through a methodological framework that combines different methods. In this context, we proceed with a diagnostic analysis of the sustainability of the Ardennes governance system. This analysis was developed from a version of the general framework for the analysis of the sustainability of socio-ecological systems developed by Ostrom. It was adapted to a large system and applied as part of a participatory research process. This identified three main vulnerabilities: the absence of an observatory of the socio-ecological system as a whole, the lack of a structured intersectoral dialogue, and the limited capacity to act of local authorities and civil society. We therefore suggest conducting prospective and retrospective analyses to identify adaptation paths of the governance system in relation to climate change. This should make it possible to design and experiment interventions to transform the governance of this large socio-ecological system towards greater sustainability.